Alfaxalone Causes Reduction of Glycinergic IPSCs, but Not Glutamatergic EPSCs, and Activates a Depolarizing Current in Rat Hypoglossal Motor Neurons - Lau, Cora; Thakre, Prajwal P.; Bellingham, Mark C. (Frontiers in Cellular Neuroscience, 2019)
We investigated effects of the neuroactive steroid anaesthetic, alfaxalone on intrinsic excitability, and on inhibitory and excitatory synaptic transmission to hypoglossal motor neurons (HMNs). Whole cell recordings were made from HMNs in brainstem slices from 7-14 day old Wistar rats. Spontaneous, miniature, and evoked inhibitory post-synaptic currents (IPSCs), and spontaneous and evoked excitatory postsynaptic currents (EPSCs) were recorded at –60mV. Alfaxalone did not alter spontaneous glycinergic IPSC peak amplitude, rise time or half width up to 10µM, but reduced IPSC frequency from 3µM. Evoked IPSC amplitude was reduced from 30nM. Evoked IPSC rise time was prolonged and evoked IPSC decay time was increased only by 10µM alfaxalone. Alfaxalone also decreased evoked IPSC paired pulse ratio (PPR). Spontaneous glutamatergic EPSC amplitude and frequency were not altered by alfaxalone, and evoked EPSC amplitude and PPR was also unchanged. Alfaxalone did not alter HMN repetitive firing or action potential amplitude. Baseline holding current at -60mV was increased in an inward direction; this effect was not seen when TTX was present. These results suggest that alfaxalone modulates glycine receptors, causing a delayed and prolonged channel opening, as well causing presynaptic reduction of glycine release, and activates a membrane current, which remains to be identified. Alfaxalone selectively reduces glycinergic inhibitory transmission to rat HMNs via a combination of pre- and post-synaptic mechanism. The net effect of these responses to alfaxalone is to increase HMN excitability and may therefore underlie neuro-motor excitation during neurosteroid anaesthesia.